CLARIFICATION OF THE CONCEPTUAL BASIS FOR INDUSTRIAL DIVERSIFICATION STRATEGY: CONSIDERING A REGIONAL CONTEXT FOR RURAL AREAS NEEDS - Dunayev, Ihor; Chernyavskiy, Kostiantyn (Pressing Problems of Public Administration, 2021)
This paper proposes clarification of the conceptual bases of the industrial diversification strategy for regions and territorial communities to meet corresponding renewing of economic their structure and to take into account the needs of Ukrainian rural areas. Such approach allows combining development of spatial theories and economic-governance approaches (such popular smart-specialization) for further drafting proposals to the responsible regional and local authorities. The material is presented according to the following logic: first, the conceptual and general theoretical “framework”, then – description of analytical approach to local opportunities and barriers to the formation of a new trajectory of industrial development, then – basic options of regional economic policy for a new regional economic strategy and its corresponding new trajectory of industrial path; the last part - features of policy formation at the local and regional levels for different types of regions. These assessments provide a basis for policy development and relevant recommendations based on the specific context of the region and the countryside.